Hearing God : developing a conversational relationship with God - Willard, Dallas, 1935-2013.; Johnson, Jan, 1952- (Downers Grove, Ill. : IVP Books, 2012)
"God spoke to me." "The Spirit spoke to my heart." "God revealed the idea to me." Being close to God means communicating with him -- telling him what is on our hearts in prayer and hearing and understanding what he is saying to us. It is this second half of our conversation with God that is so important but that can also be so difficult. How do we hear his voice? How can we be sure that what we think we hear is not our own subconscious? What role does the Bible play? What if what God says to us is not clear? The key, says best-selling author Dallas Willard, is to focus not so much on individual actions and decisions as on building our personal relationship with our Creator. In this updated and expanded edition of Willard's beloved book, originally published as In Search of Guidance, you'll gain rich spiritual insight into how we can hear God's voice clearly and develop an intimate partnership with him in the work of his kingdom. Including new material from Dallas Willard's teaching at the Renovare Institute and reformatted to be even easier to read, this classic continues to endure as one of today's best resources for learning to listen closely to God. - Publisher.
A word from the author -- Preface -- A paradox about hearing God : why do people say they hear God but so few can explain it? -- Guidelines for hearing from God : what are some common misunderstandings? -- Hearing God in scripture : 1 Kings 19:2-18 -- Never alone : how is God with us? -- Our communicating cosmos : does God really talk to people? -- Hearing God in scripture : 2 Kings 6:11-17 -- The still, small voice and its rivals : how has God spoken to people before? -- Hearing God in scripture : Proverbs 20:27; 1 Corinthians 2:9-13, 15-16 -- The Word of God and the rule of God : what part does God's Word have in everyday reality? -- Hearing God in scripture : Psalm 19:1-6; 119:89-91 -- Redemption through the Word of God : how does hearing God lead to character transformation? -- Hearing God in Scripture: Romans 5:10-11; 6:4, 8-11 -- Recognizing the voice of God : how do we know we are hearing God and not our own voices? -- Hearing God in scripture : 1 Chronicles 14:8-17 -- A life more than guidance : how do we learn to listen to God? -- Epilogue : The way of the burning heart -- Appendix : Key questions and answers.
Includes bibliographical references (p. [296]-302) and index.
Keywords: Spiritual life -- Christianity; God (Christianity) -- Will